ANALISIS PERBANDINGAN EFISIENSI BANK UMUM SYARIAH DAN BANK UMUM KONVENSIONAL DENGAN MENGGUNAKAN METODE DATA ENVELOPMENT ANALYSIS - IFANDA AKBAR, RIZKA; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2018)
This study aims to determine the difference in average efficiency between sharia commercial banks and conventional commercial banks after the onset of global financial crisis in 2008 during 2010 to 2016. Bank efficiency calculations performed using nonparametric method Data Envelopment Analysis (DEA) Intermediation approach model Variable Return To Scale (VRS) output-oriented. Hypothesis test is done by using Mann Whitney U-Test. The results of this study indicate that there is no difference between the average efficiency of sharia banks and conventional commercial banks because the input and output variable values ??of each bank also didn?t show significant difference during the study period.